2019
DOI: 10.3126/njh.v16i2.26293
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatic Heart Disease in school going children: A cross-sectional epidemiological profile of Jajarkot, Nepal

Abstract: Background and Aims: Rheumatic Heart Disease (RHD) is the most common heart disease among children and young adults in Nepal. Identifying the prevalence of RHD is important in planning RHD prevention program. There are few studies on RHD conducted among children of unreached population of Nepal. This study aimed to determine the epidemiological status of RHD among school going children living in rural and underdeveloped community of Jajarkot, Nepal. Methods: This is a cross-sectional study of 6,147 schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
(13 reference statements)
0
5
0
Order By: Relevance
“… 14 A similar study conducted in Jajarkot, Nepal, documented an overall prevalence of RHD of 7.32 per thousand school children. 15 Another study carried out among 26 schools in the Sunsari district located in eastern Nepal documented a high prevalence of borderline and definite RHD, which was 10·2 (95% CI: 7·5–13·0) per 1000 children. 5 The study used echocardiography as a screening method.…”
Section: Discussionmentioning
confidence: 98%
“… 14 A similar study conducted in Jajarkot, Nepal, documented an overall prevalence of RHD of 7.32 per thousand school children. 15 Another study carried out among 26 schools in the Sunsari district located in eastern Nepal documented a high prevalence of borderline and definite RHD, which was 10·2 (95% CI: 7·5–13·0) per 1000 children. 5 The study used echocardiography as a screening method.…”
Section: Discussionmentioning
confidence: 98%
“…Meanwhile, echo-based screening for children with RHD in school revealed a higher prevalence of RHD in girls, but there was no significant difference. [ 14 ] The relationship between RHD and gender in unclear, but intrinsic factor such as autoimmune sensitivities and extrinsic factors such as greater exposure to group A beta-hemolytic streptococcal infections in female may explain this relationship. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…A large epidemiological survey among school children in the capital Kathmandu valley reported the prevalence to be 0.90 per thousand (in the age group 5–16 years) which was significantly lower than the prevalence in a remote western district Jajarkot having the prevalence of 7.32 per thousand schoolchildren. This showed the alarming prevalence in underprivileged children living in resource constrained environment and poor access to health care on the one hand and underlined the success of primary and secondary prevention programs in the capital on the other [ 6 , 7 ]. Other studies reported the prevalence of definite RHD as 1.66% in schoolchildren in central Nepal and 1 in 100 schoolchildren in Eastern Nepal [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%